Beneficial Effects of Polydeoxyribonucleotide (PDRN) in an In Vitro Model of Fuchs Endothelial Corneal Dystrophy - Ida Ceravolo; Federica Mannino; Natasha Irrera; Letteria Minutoli; Vincenzo Arcoraci; Domenica Altavilla; Gian Maria Cavallini; Salvatore Guarini; Francesco Squadrito; Giovanni Pallio (MDPI AG, 2022)
Fuchs endothelial corneal dystrophy (FECD) is a bilateral, hereditary syndrome characterized by progressive irreversible injury in the corneal endothelium; it is the most frequent cause for corneal transplantation worldwide. Oxidative stress induces the apoptosis of corneal endothelial cells (CECs), and has a crucial function in FECD pathogenesis. The stimulation of the adenosine A2A receptor (A2Ar) inhibits oxidative stress, reduces inflammation and modulates apoptosis. Polydeoxyribonucleotide (PDRN) is a registered drug that acts through adenosine A2Ar. Thus, the goal of this study was to assess the effect of PDRN in an in vitro FECD model. Human Corneal Endothelial Cells (IHCE) were challenged with H2O2 (200 μM) alone or in combination with PDRN (100 μg/mL), PDRN plus ZM241385 (1 μM) as an A2Ar antagonist, and CGS21680 (1 μM) as a well-known A2Ar agonist. H2O2 reduced the cells' viability and increased the expression of the pro-inflammatory markers NF-κB, IL-6, IL-1β, and TNF-α; by contrast, it decreased the expression of the anti-inflammatory IL-10. Moreover, the pro-apoptotic genes Bax, Caspase-3 and Caspase-8 were concurrently upregulated with a decrease of Bcl-2 expression. PDRN and CGS21680 reverted the negative effects of H2O2. Co-incubation with ZM241385 abolished the effects of PDRN, indicating that A2Ar is involved in the mode of action of PDRN. These data suggest that PDRN defends IHCE cells against H2O2-induced damage, potentially as a result of its antioxidant, anti-inflammatory and antiapoptotic properties, suggesting that PDRN could be used as an FECD therapy.